Parental rights, best interests and significant harms: who should have the final say over a child's medical care? - Auckland, C; Goold, I (Cambridge University Press, 2019)
Who should have the ultimate say over a child’s medical treatment? A series of high-profile withdrawal of care cases have highlighted the full extent of the courts’ authority to make deci-sions on behalf of children in the medical context. In both the Charlie Gard and Alfie Evans litigation, the courts have made clear that they have the power to make medical decisions for children at the point that child’s welfare is engaged. All courts involved in both cases affirmed the orthodox position that the threshold for judicial intervention in disputes about medical care of children is the welfare of the child, often referred to as the “best interests” approach (refer-ring to both the threshold and the test applied to determine what should be done). While no new point of law has been decided in these cases, they are important in that they confirm just how expansive the inherent jurisdiction of the courts in such cases is, extending as far as to prevent parents from removing their child to another jurisdiction to pursue alternative treat-ment. In this paper, we argue that the current threshold for intervention is too low. We argue that prima facie decision-making authority about a child’s medical care should rest with the child’s parents, affording them the ability to choose between the range of medical options available. This authority should yield only where the parents’ decision carries a “serious risk of significant harm” to the child, at which point the court then has the authority to intervene. When it does so, the court should then apply the best interests approach.